Prevalence and predictors of metabolic syndrome in women with polycystic ovarian syndrome: a study from Southern India - Varghese, Jisha; Kantharaju, Supriya; Thunga, Suchitra; Joseph, Nitin; Singh, Prakhar Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Metabolic syndrome (MBS) is a common disorder and is thought to be highly prevalent in polycystic ovarian syndrome (PCOS). The objectives were to find out the prevalence and predictors of metabolic syndrome in women with PCOS. Methods: Forty five women diagnosed with PCOS, underwent clinical and laboratory assessments for the diagnosis of metabolic syndrome, as per modified National Cholesterol Education Program’s Adult Treatment Panel III (NCEP ATP III criteria). Results: Twenty four (53.3%) subjects had metabolic syndrome. The prevalence of individual components of the metabolic syndrome among PCOS patients were: waist circumference ≥80 cm in 36 (86.6%), High Density Lipoprotein (HDL-C) less than 50 mg/dl in 42 (93.3%), triglycerides ≥150 mg/dl in 17 (37.8%), blood pressure ≥130/85 mmHg in 7 (15.6%), and fasting plasma glucose ≥100 mg/dl in 13 (28.8%). Subjects with MBS had significantly higher BMI compared to those without (P = 0.039). However, fasting insulin and free testosterone levels did not differ significantly between subjects with and without MBS. Conclusions: The metabolic syndrome and its individual components, waist circumference ≥80 cm in particular were found to be common among PCOS patients in this study. This along with high BMI being significantly associated with MBS suggests immediate need of interventions like lifestyle changes for prevention of MBS and other cardiovascular diseases. Also, as dyslipidemia was more common than impaired fasting glucose among PCOS patients, finding of one risk factor should prompt the clinician to search for other risk factors.